2017
DOI: 10.1530/endoabs.50.p339
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Obstructive Sleep Apnoea in women with Polycystic Ovary Syndrome: a Systematic Review and Meta-analysis

Abstract: Background Obesity is a common risk factor for polycystic ovary syndrome (PCOS) and obstructive sleep apnoea (OSA). Both PCOS and OSA are associated with increased risk of type 2 diabetes and cardiovascular disease. Hence, it is important to determine the burden of OSA in women with PCOS. Methods We searched electronic databases (MEDLINE, Embase, CINAHL, PsycINFO, Scopus, Web of Science, OpenGrey, CENTRAL), conference abstracts, and reference lists of relevant articles, up to January 2019. No restriction for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Home use of continuous positive airway pressure (CPAP) therapy OSA exhibits high prevalence among women with PCOS and obesity, attributed at least partly to hyperandrogenism and central adiposity, and further aggravates the adverse cardio-metabolic profile of these patients [19,25,80,81]. As OSA may cause various degrees of reduced arterial oxygen saturation and additional cardio-metabolic complications, routine CPAP home use is often indicated in women with PCOS and OSA [19,25,80,81]. However, because CPAP is regarded as a high-risk aerosol-generating procedure which may increase the risk of SARS-CoV-2 transmission to other household members, routine CPAP therapy at home has been the subject of recent debate [82][83][84].…”
Section: Antihypertensive Medicationsmentioning
confidence: 99%
“…Home use of continuous positive airway pressure (CPAP) therapy OSA exhibits high prevalence among women with PCOS and obesity, attributed at least partly to hyperandrogenism and central adiposity, and further aggravates the adverse cardio-metabolic profile of these patients [19,25,80,81]. As OSA may cause various degrees of reduced arterial oxygen saturation and additional cardio-metabolic complications, routine CPAP home use is often indicated in women with PCOS and OSA [19,25,80,81]. However, because CPAP is regarded as a high-risk aerosol-generating procedure which may increase the risk of SARS-CoV-2 transmission to other household members, routine CPAP therapy at home has been the subject of recent debate [82][83][84].…”
Section: Antihypertensive Medicationsmentioning
confidence: 99%
“…Data are presented as mean or mean ± s.d. compared to controls, and the relationship between OSA severity and hyper-androgonaemia were not consistent across the studies (347). This could be due to the low circulating androgen levels in women with PCOS compared to men.…”
Section: Osa and Polycystic Ovarian Syndrome (Pcos)mentioning
confidence: 83%
“…OSA is highly prevalent in women of reproductive age with PCOS. A recent systematic review and meta-analysis from our group (15 studies, n = 568) showed that 36.1% (95% CI: 22.4-51.0) of women with PCOS had OSA regardless of the PCOS definition used (347). In addition, OSA prevalence was significantly higher in obese women with PCOS compared to lean (OR: 3.96, 95% CI: 1.…”
Section: Osa and Polycystic Ovarian Syndrome (Pcos)mentioning
confidence: 93%
See 2 more Smart Citations